The development of SMEs in China: Opportunities and Challenges - Luo, Murong; Hussein Al-Shami, Samer Ali; Binti Mansor, Nusaibah (Opción, 2019)
Purpose-The purpose of this study is to propose a framework of Chinese SMEs’ development in recent years, and to present the opportunities and challenges for SMEs. Design/methodology/approach-The research of this paper is based on the collection and evaluation of existing literature, year- books, and government disclosures. Previous literature is mainly collected from Science Direct, Scopus, Google Scholar, etc. Findings-This study finds that, SMEs have experienced rapid development, financial crisis and stable growth period since 2001. Escalation of consumption structure, globaliza- tion, and cross-border e-commerce platforms have provided new opportuni- ties for SMEs. However, financing constraints, squeezed profit margins and innovation difficulties have become the most prominent challenges facing by SMEs. Originality/value-This study presents a development overview of Chinese SMEs, and emphasizes the opportunities and challenges. The result of this study can provide a basis for future research and policy formulation.